Advances in Research on the Effects and Mechanisms of Chemokines and Their Receptors in Cancer - Xu, Jing; Li, Jing-quan; Chen, Qi-lei; Shestakova, Elena A.; Misyurin, Vsevolod A.; Pokrovsky, Vadim S.; Tchevkina, Elena M.; Chen, Hu-biao; Song, Hang; Zhang, Jian-ye (Frontiers in Pharmacology, 2022)
Cancer is a common and intractable disease that seriously affects quality of life of patients and imposes heavy economic burden on families and the entire society. Current medications and intervention strategies for cancer have respective shortcomings. In recent years, it has been increasingly spotlighted that chemokines and their receptors play vital roles in the pathophysiology of cancer. Chemokines are a class of structurally similar short-chain secreted proteins that initiate intracellular signaling pathways through the activation of corresponding G protein-coupled receptors and participate in physiological and pathological processes such as cell migration and proliferation. Studies have shown that chemokines and their receptors have close relationships with cancer epigenetic regulation, growth, progression, invasion, metastasis, and angiogenesis. Chemokines and their receptors may also serve as potential targets for cancer treatment. We herein summarize recent research progresses on anti-tumor effects and mechanisms of chemokines and their receptors, suggesting avenues for future studies. Perspectives for upcoming explorations, such as development of multi-targeted chemokine-based anti-tumor drugs, are also discussed in the present review.